Preparedness for Paediatric CPR amongst Doctors in Cape Town - Amien, Nabeela (Department of Public Health and Family Medicine, 2022)
Background: CPR is the principal medical intervention used to reduce the high mortality associated with cardiorespiratory arrest. There is a paucity of literature on the preparedness for paediatric CPR (pCPR) amongst doctors in Cape Town. The study aimed to assess the preparedness for pCPR of doctors working in Western Cape Provincial Government primary healthcare facilities (PHCFs) in Cape Town with regard to knowledge, confidence and doctors' knowledge of equipment availability. Methods: A cross-sectional descriptive-analytic study using a self-developed questionnaire to collect quantitative data from a sample of 206 doctors working in Cape Town PHCFs. Results: 173 doctors (84% response rate) completed the questionnaire. The majority (81.8%) had not done a pCPR course (Paediatric Advanced Life Support or Advanced Paediatric Life Support). 88.3% had done Basic Life Support; 28% >2 years ago. The average pCPR knowledge score was 61% (SD=20.3, range 8.3-100%). Doctors doing their community service and internship had significantly higher knowledge scores compared to Grade 3 medical officers (p = .001 and .010 respectively). 11% had performed pCPR >10 times in the past year; 20% had never performed pCPR, and 35% did not feel confident performing pCPR. More than 35% of doctors were uncertain about the availability of equipment in their facility. Conclusion: Doctors working in Cape Town PHCFs are poorly prepared to perform pCPR. Doctors' knowledge of pCPR and availability of equipment is inadequate and confidence in their ability to perform pCPR is low. Formal pCPR training and education on equipment location and availability is recommended.